Analysis of The Effect of Profitability and Liquidity on Income Management Which Impact on Company Value in Soe Banks Registered on Indonesia Stock Exchange Period 2009-2019 - Marjohan, Masno (CV. Ridwan Publisher, 2021)
This study aims to analyze, test the effect of profitability as measured by Return On Assets, liquidity as measured by LDR on earnings management, and the impact of earnings management on firm value in state-owned tire companies listed on the Indonesia Stock Exchange from 2009 to 2019. Total population This research is 4 state-owned bank companies so that the entire population is sampled with a period of 10 years from 2009-2019. The analysis technique used in this research is panel data regression to obtain a comprehensive picture of the relationship between one variable and another. The results of the research partially show that ROA, LDR Profitability has no effect on Earning Management, Profitability and Liquidity simultaneously have an effect on Earnings Management, and show that earnings management affects Firm Value.